Glycaemic outcomes in adults with type 1 diabetes transitioning towards advanced automated insulin delivery systems – a real-world analysis at a Swiss tertiary centre (Swiss Medical Weekly, 2023)
AIMS OF THE STUDY: To assess glucose levels in adults with diabetes at a Swiss tertiary hospital when transitioning from insulin delivery with a sensor-augmented pump with (predictive) low-glucose suspend ([P]LGS) to a hybrid-closed loop (HCL) and from a HCL to an advanced hybrid-closed loop (AHCL).METHODS: Continuous glucose monitoring data for 44 adults with type 1 diabetes transitioning from (P)LGS to hybrid-closed loop and from hybrid-closed loop to advanced hybrid-closed loop were analysed, including the percentage of time spent within, below, and above glucose ranges. In addition, a subgroup analysis (n = 14) of individuals undergoing both transitions was performed.RESULTS: The transition from a (P)LGS to a hybrid-closed loop was associated with increased time in range (6.6% [2.6%–12.7%], p